A new species of Chimarra (Otarrha) Blahnik from Brazil (Trichoptera: Philopotamidae) - Camargos, Lucas Marques De (Zootaxa, 2016)
Chimarra Stephens, 1829 is the second largest genus of Trichoptera, with more than 700 extant species worldwide (Morse 2015). Currently 4 subgenera are recognized: Chimarra Stephens, 1829, known from all zoogeographic regions; and Curgia Walker, 1860, Chimarrita Blahnik, 1997, and Otarrha Blahnik, 2002, all of them confined to the Neotropics (Blahnik & Holzenthal 2012).